Audio–visual aid in teaching "fatty liver". Issue 3 (2nd December 2015) - Dash, Sambit; Kamath, Ullas; Rao, Guruprasad; Prakash, Jay; Mishra, Snigdha
Abstract: Use of audio visual tools to aid in medical education is ever on a rise. Our study intends to find the efficacy of a video prepared on "fatty liver, " a topic that is often a challenge for pre‐clinical teachers, in enhancing cognitive processing and ultimately learning. We prepared a video presentation of 11:36 min, incorporating various concepts of the topic, while keeping in view Mayer's and Ellaway guidelines for multimedia presentation. A pre–post test study on subject knowledge was conducted for 100 students with the video shown as intervention. A retrospective pre study was conducted as a survey which inquired about students understanding of the key concepts of the topic and a feedback on our video was taken. Students performed significantly better in the post test (mean score 8.52 vs. 5.45 in pre‐test), positively responded in the retrospective pre‐test and gave a positive feedback for our video presentation. Well‐designed multimedia tools can aid in cognitive processing and enhance working memory capacity as shown in our study. In times when "smart" device penetration is high, information and communication tools in medical education, which can act as essential aid and not as replacement for traditional curriculums, can be beneficial to the students. © 2015 by The International Union of Biochemistry and Molecular Biology, 44:241–245, 2016.